Nuprl Rule : multiplyEquality

This rule proved as lemma rule_arithop_equality_true3 in file rules/rules_arith.v
 at https://github.com/vrahli/NuprlInCoq  

H  ⊢ (m1 n1) (m2 n2) ∈ ℤ

  BY multiplyEquality ()
  
  H  ⊢ m1 m2 ∈ ℤ
  H  ⊢ n1 n2 ∈ ℤ



Definitions occuring in rule :  multiply: m equal: t ∈ T int: axiom: Ax

Latex:
H    \mvdash{}  (m1  *  n1)  =  (m2  *  n2)

    BY  multiplyEquality  ()
   
    H    \mvdash{}  m1  =  m2
    H    \mvdash{}  n1  =  n2



Date html generated: 2016_12_14-AM-08_53_36
Last ObjectModification: 2016_07_08-PM-03_48_51

Theory : rules


Home Index